Proposal of a Tool for Integrating BIM and Financial Decisions in Construction Projects (2019)
The central decisions of construction projects are taken in their initial phases. Additionally, proper planning determines the success or failure of the execution, operation, and maintenance of this kind of projects. The methodology so-called Building Information Modeling (BIM) improves the result of planning through the implementation of digital models in decision making. In the current applied research, a computational tool is proposed to supporting the financial decision making in the feasibility phase by integrating cash flows and 4D models to planning. This tool allows improves the performance of planning by increasing the precision of the results of the financial indicators that are analyzed for the execution of construction projects.